Identification of the antimicrobial fraction of Mimosa tenuiflora extract - Borges, Ivanildo Viana; Cavalcanti, Leonardo Sousa; Neto, Acácio Figueirêdo; Almeida, Jackson ROBERTO Roberto Guedes da Silva; Rolim, Larissa Araújo; Araújo, Edigenia Cavalcante da Cruz (Comunicata Scientiae, 2017)
In the search of molecules and antifungal compounds with low hazard, it is important the compound inespecific action, since there is a possibility of inactivity due to the resistance development. In order to increase the alternatives for the Curvularia inaequalis and Colletotrichum gloeosporioides control, husks of M. tenuiflora were collected and processed for obtaining the aqueous extract, which was then fractionated by column chromatography, thin layer chromatography and analysed by high-performance liquid chromatography (HPLC), aiming the identification of active compounds. After obtaining the phases, germination tests were carried out with C. inaequalis. The phase “one” showed the presence of flavonoids catechin and apigenin. This phase presented degradation or inhibition of chitin layer formation in C. inaequalis and the other phases presented no activity for the evaluated concentrations. Catechin also presented inhibition of C. inaequalis germination. For the evaluation of the effect of crude extract on C. gloeosporioides germination, all concentrations were effective in inhibiting germination, and when 4 mg.mL-1 or higher concentrations were used, the inhibition was 100%. The phase “one” and the catechin inhibit the C. inaequalis germination and the crude extract inhibited, similarly to phase “one”, the germination of C. gloeosporioides.